Cyberbullying sebagai Tindak Pidana : Kajian Hukum Pidana di Era Digital - Aldi Setyo Triza Herman (Referendum : Jurnal Hukum Perdata dan Pidana, 2025)
Cyberbullying has become a significant social problem in the digital era, requiring comprehensive legal handling. This research analyzes cyberbullying as a form of digital crime and how Indonesian law regulates, handles, and faces challenges in law enforcement in the digital era. This study uses a normative juridical approach with library research methods. The results show that although Indonesia does not yet have specific laws governing cyberbullying, several provisions in existing laws and regulations can be used to ensnare cyberbullying perpetrators. However, the unique characteristics of cyberbullying and the dynamics of technological development pose challenges in law enforcement that require regulatory updates and increased capacity of law enforcement officers. Prevention and countermeasures require a holistic approach involving legal, technological, educational and social aspects.